Effectiveness of Controversial Issues Learning Model Through Problem Based Learning in Improving Students Critical Thinking Skills - Hadi Hartono; Sinaga, Risma Margaretha; Pujiati (International Journal of Educational and Life Sciences, 2024)
This study is to determine the effect of controversial issues learning model and problem-based learning model in improving the critical thinking ability of Pancasila and Citizenship Education students at State Junior High School 14 Krui. The research method used is a quantitative approach with the method used quasi-experiment or pseudo-experiment. The research design is pretest and posttest Control Groub. Research Results There is an effect of controversial issues learning model through problem based learning on the critical thinking ability of students before and after learning using controversial issues learning model through problem based learning obtaining Sig value. 0.000 <0.05 so that H0 is rejected and Ha is accepted. This means that the results of the critical thinking skills of Pancasila Education and Citizenship of students through problem-based learning models can have a positive and effective influence in improving the critical thinking skills of students and through these two learning models can establish good communication with classmates so that learning can take place with a conducive, interactive, dynamic, open, interesting and fun atmosphere.